Risk and benefit of neoadjuvant therapy among patients undergoing resection for non-small-cell lung cancer. (13th December 2017) - Yendamuri, Sai; Groman, Adrienne; Miller, Austin; Demmy, Todd; Hennon, Mark; Dexter, Elisabeth; Picone, Anthony; Nwogu, Chukwumere; Dy, Grace K
Abstract: OBJECTIVES: Neoadjuvant therapy has emerged as a favoured treatment paradigm for patients with clinical N2 disease undergoing surgical resection for non-small-cell lung cancer. It is unclear whether such a treatment paradigm affects perioperative outcomes. We sought to examine the National Cancer Database (NCDB) to assess the impact of neoadjuvant therapy on perioperative outcomes and long-term survival in these patients. METHODS: All patients with a history of non-small-cell lung cancer undergoing anatomical resection between 2004 and 2014 were included. Thirty-day and 90-day mortality of all patients having neoadjuvant therapy versus those who did not were compared. In addition, the impact of neoadjuvant therapy on the overall survival of patients with clinical N2 disease was examined. RESULTS: Of the 134 428 selected patients, 9896 (7.4%) patients had neoadjuvant chemotherapy. Patients undergoing neoadjuvant therapy had a higher 30-day (3% vs 2.6%; P < 0.01) and 90-day mortality (6.5% vs 4.9%; P < 0.01). This association remained after adjusting for covariates. Among patients with clinical N2 disease ( n = 10 139), 42.3%, 35.3% and 22.4% of patients had neoadjuvant, adjuvant and no chemotherapy, respectively. Univariable, multivariable and propensity score-weighted analyses indicated no difference in survival between patients receiving neoadjuvant and adjuvant chemotherapy. CONCLUSIONS: Neoadjuvant therapy may adversely affect perioperative outcomes without providing a survival advantage compared with adjuvant therapy in clinical N2 stage patients. Randomized controlled trials need to be conducted to examine this issue further.